Pendampingan Kelompok Kerja Guru IPAS SDN Berbasis Technological Pedagogical and Content Knowledge di Desa Sampali. Percut Sei Tuan, Deli Serdang - Hidayat; Setiawan, Deny; Amin Fauzi (Pelita Masyarakat, 2025)
Technological Pedagogical and Content Knowledge (TPACK) is an approach that integrates knowledge of technology, pedagogy, and content according to the learning context. Understanding, skills, and application of TPACK in learning by elementary school teachers are needed in today's digital technology era. The use of TPACK-based media and integrating it into the learning process allows learning materials to be packaged in an interesting, contextual and needed way for elementary school students. However, in reality, the understanding and skills of elementary school teachers are still low, and they have not utilized TPACK in learning. On that basis, a partnership network was built to assist in improving teachers' understanding and skills in developing TPACK-based animation media. The assistance activity involved the Teacher Working Group, which was carried out at SD Negeri 101774, Sampali Village. The assistance method was carried out through the stages of preparation, implementation, monitoring, and/or evaluation and follow-up. The results of the assistance showed an increase in teachers' understanding and skills about TPACK, increased utilization and application of TPACK in learning, and the creativity of teachers in developing TPACK-based animation media in the learning process.